Catch Composition of Set Net Fisheries during Normal Season in Sungai Sembilang Waters, Selangor, Malaysia - Wan Muhammad Luqman bin Wan Rosdi; Abdul Wahab Abdullah; Mohd Nazir Taib; Noor Hanis Abu Halim; Nur Habibah Abu Talib; Hashim Shuhaimi; Sharum Yusof (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • The Set Net was identified and recorded. • Length and weight of the catch of set net was analyzed.